The Application of Waterfall Model in The Design of Zakat Management Information System at DKM Baiturrahman - Didih Aditiyawarman; Saeful Mu’alim (Ridwan Institute, 2022)
The process of receiving zakat is very sensitive because zakat receipts are included in the category of financial management that needs to be accounted for in reporting. DKM Baiturrahman Mosque is one of the institutions that carry out the process of receiving zakat, where the process of receiving zakat is carried out and managed using a manual or conventional system, reporting recapitulation still uses the manual method so that data recording still has several weaknesses such as vulnerability to data loss, data search that takes time quite a long time and poor data accuracy. Therefore, it is necessary to build an information system for zakat management by using a good information technology. This application is called SIPEZAK (Sistem Informasi Pengelolaan Zakat). The development of this website-based zakat management application is built using the waterfall model approach. With this information system, it is hoped that it will help the process of receiving zakat, distributing and reporting zakat funds to be more effective and efficient